2013
DOI: 10.1159/000350424
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-33 Synergistically Enhances Immune Complex-Induced Tumor Necrosis Factor Alpha and Interleukin-8 Production in Cultured Human Synovium-Derived Mast Cells

Abstract: Background: Substantial evidence suggests that human synovial mast cells (MCs) are involved in the pathogenesis of rheumatoid arthritis (RA). Interleukin (IL)-33 is believed to play an important role in the pathogenesis of RA. We recently reported that FcγRI is responsible for producing abundant tumor necrosis factor alpha (TNF-α) from cultured synovium-derived MCs (SyMCs) in response to aggregated immunoglobulin G (IgG). However, whether or not IL-33 affects immune complex (IC)-induced synovial MC activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 19 publications
(25 reference statements)
1
17
0
Order By: Relevance
“…In mouse models of arthritis involving active immunization, the use of ST2 KO mice, ST2 blockade, or injection of sST2 decreased immune responses and severity of arthritis. This finding suggested a pathogenic role for IL-33, signaling through ST2L, in these experimental models (20)(21)(22). However, although arthritis is reduced in ST2 KO mice, it did not differ in IL-33 KO mice compared with wild-type mice (25,26).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In mouse models of arthritis involving active immunization, the use of ST2 KO mice, ST2 blockade, or injection of sST2 decreased immune responses and severity of arthritis. This finding suggested a pathogenic role for IL-33, signaling through ST2L, in these experimental models (20)(21)(22). However, although arthritis is reduced in ST2 KO mice, it did not differ in IL-33 KO mice compared with wild-type mice (25,26).…”
Section: Discussionmentioning
confidence: 77%
“…IL-33 levels in serum and synovial fluid are elevated, and a strong IL-33 expression can be detected in RA synovium (19,20). IL-33 synergistically enhances immune complex-induced TNF-a and IL-8 production in cultured human synovium-derived mast cells (21). In mouse models, whereas arthritis is reduced in ST2 knockout (KO) or in anti-ST2-treated mice x Institut de Pharmacologie et de Biologie Structurale CNRS-Université de Toulouse III, F-31000 Toulouse, France; and (22)(23)(24), it does not differ in IL-33 KO mice compared with wild-type mice (25,26).…”
mentioning
confidence: 99%
“…IL-1 receptorlike 1, encoded by IL1RL1, is a receptor for IL-33. IL1RL1 is induced by proinflammatory stimuli, and IL1RL1, like IL-6, is implicated in inflammation-associated disease states (26)(27)(28).…”
Section: Resultsmentioning
confidence: 99%
“…Choi et al [27] reported that hesperidin reduced the expression of TNF-α by suppressing HIF-1α in mast cells. TNF-α is released from mast cells by degranulation and aggravates allergic symptoms by inducing neutrophil chemotaxis and the production of other inflammatory cytokines [28,29,30]. Our results show that Buk music down-regulated TNF-α protein levels, which suggests Buk music down-regulated TNF-α by inhibiting HIF-1 activation.…”
Section: Discussionmentioning
confidence: 68%